Mapping of a novel locus for achromatopsia (ACHM4) to 1p and identification of a germline mutation in the α subunit of cone transducin (GNAT2). Issue 9 (1st September 2002) - Aligianis, I A; Forshew, T; Johnson, S; Michaelides, M; Johnson, C A; Trembath, R C; Hunt, D M; Moore, A T; Maher, E R
Abstract : Objective: To determine the molecular basis for achromatopsia using autozygosity mapping and positional candidate gene analysis. Design and methods: A large consanguineous Pakistani family containing six subjects with autosomal recessive complete achromatopsia was ascertained. After excluding linkage to the two known achromatopsia genes ( CNGA3 and CNGB3 ), a genome wide linkage screen was undertaken. Results: Significant linkage was detected to a 12 cM autozygous segment between markers D1S485 and D1S2881 on chromosome 1p13. Direct sequence analysis of the candidate gene GNAT2 located within this interval identified a frameshift mutation in exon 7 (c842_843insTCAG; M280fsX291) that segregated with the disease. Conclusions: The GNAT2 gene codes for cone α-transducin, the G protein that couples the cone pigments to cGMP-phosphodiesterase in phototransduction. Although cone α-transducin has a fundamental role in cone phototransduction, mutations in GNAT2 have not been described previously. Since mutations in the CNGA3 gene may cause a variety of retinal dystrophies (complete and incomplete achromatopsia and progressive cone dystrophy), GNAT2 mutations may also prove to be implicated in other forms of retinal dystrophy with cone dysfunction.